The Science and Politics of Work Disability Prevention - Brouwer, Sandra; Boot, Cécile RL (Scandinavian Journal of Work, Environment & Health, 2019)
This book focusses on one of today’s biggest social and labor market challenges: how to deal with the rising cost of illness and disability benefits across advanced economies. It reflects on the development and evaluation of activation-oriented work disability policies in 13 countries, aiming to tighten the inflow of benefit recipients and to maximize labor-force participation of people with disabling health conditions. The book is divided in four parts and comprises 16 chapters, written by well-positioned researchers in the field of work disability. The first part includes two chapters. Chapter 1 starts with a broad overview of the developments in the field of work disability policy and research over the past decades. In Chapter 2, Patrick Loisel reflects on the Sherbrooke Model for return to work by describing the rationale for developing the model, the successful adoption of the model in work disability research internationally and about his personal experiences of implementing the model in daily practice which gives a nice view of how the implementation of models is highly dependent on contextual factors. The chapters 3-15 contain detailed analyses of work disability systems of the various countries. The chapters are organized per country and divided in two parts: caused-based welfare systems (part 2), ie, illness and disability benefits are paid directly or indirectly by employers, and comprehensive social security systems (part 3), ie, general tax revenues are used to pay for the costs. Part 2 includes five chapters with information about the United States, Canada, Australia, New Zealand and China. Part 3 includes eight chapters with information about Sweden, Finland, France, Germany, Switzerland, Belgium, the Netherlands and the United Kingdom. Part four closes with a chapter synthesizing the previous chapters and reflecting on the trends and on future directions in work disability policy. The authors identified and described four key strategies taken similar across jurisdictions, ie, part-time sick-leave benefits, timing of early return to work, duration of work disability benefits and vocational rehabilitation. Furthermore, the authors discuss some key gaps across international work disability policies, such as problems of labor demand, uneven access to work disability benefits and services, and mental health disability. A strong feature of the book is the interdisciplinary approach followed by the editor. The book includes a variety of expertise in the field of work disability and social security, from law, medicine, psychology, epidemiology, political and social sciences. Another strength is that this book provides the reader with an up-to-date overview of many of the current political realities in up to 13 countries, which are the key to understanding work disability policy change and implementation over the past decades. The last chapter provides an overview of challenges, opportunities, and values for work disability policy, which is useful for agenda setting. For example, the rise of work-related mental illness is discussed, matching the increasing prevalence of mental health problems at the workplace. Where the cause-based systems mainly consisted of dealing with musculoskeletal disorders in the past, more systems are now exploring how to compensate work-related mental health problems, albeit in very different ways. As work-related mental health problems are expected to increase in the future, supporting compensation systems are crucial for this growing group of vulnerable workers. The ambitious question posed in the first chapter, why one jurisdiction took a particular route to improve work integration and another took a different route, and insight into context that shaped different pathways, is not fully answered. Describing the state of affairs per country in details makes it difficult to compare systems between countries, as the focus per chapter differs. A systematic comparison would have equipped the reader with essential information across jurisdictions in order to distil core successful approaches. Moreover, the distinction between cause-based and comprehensive systems made in the first chapter, raised expectations about a comparison of both systems in this final chapter, which would have been of added value to the reader. However, a critical reflection of the effectiveness of policies developed for cause-based or comprehensive systems is missing in the final chapter. Providing an overview of the literature of trials on return to work policies and interventions in this field would have been of added value to gain insight into what is and what is not yet known. For example, two recent studies in the Scandinavian Journal of Work, Environment and Health showed that integrating workplaces into prevention programs show promising results regarding effectiveness in preventing or reducing health problems and time to return-to-work in both workers with musculoskeletal disorders (1) as well as mental conditions (2). Moreover, the study of Viikari-Juntura et al (3) showed the effectiveness of the introduction of a Finnish legislation on of the use of part-time sick leave at the early stage of work disability on both return to work and work participation. These examples all show the relevance of intervention strategies at the level of the workplace and legislation that are useful for agenda setting in our research field. Overall, the various authors provide an interesting and complete overview of the development and evolution of work disability policies in 13 countries that is of interest for scientist in the field of work and health, but also social security policymakers, scholars, and students in the field of public health and social sciences. 1. Stock SR, Nicolakakis N, Vézina N, Vézina M, Gilbert L, Turcot A et al. Are work organization interventions effective in preventing or reducing workrelated musculoskeletal disorders? A systematic review of the literature. Scand J Work Environ Health. 2018;44(2):113–133. https://doi.org/10.5271/sjweh.3696 2. Dalgaard VL, Aschbacher K, Andersen JH, Glasscock DJ, Willert MV, Carstensen O, Biering K. Return to work after work-related stress: a randomized controlled trial of a work-focused cognitive behavioral intervention. Scand J Work Environ Health. 2017 Sep 1;43(5):436-446. https://doi.org/10.5271/sjweh.3655 3. Viikari-Juntura E, Virta LJ, Kausto J, Autti-Rämö I, Martimo K-P, Laaksonen M, et al. Legislative change enabling use of early part-time sick leave enhanced return to work and work participation in Finland. Scand J Work Environ Health. 2017;43(5):447–456. https://doi.org/10.5271/sjweh.3664
Keywords: book review; prevention; work disability; work disability prevention